International Islamic digital library a Malaysian initiative - Perpustakaan Negara Malaysia (Kuala Lumpur : National Library of Malaysia)
The International Islamic Digital Library project calls for a global collaborative effort in making it a comprehensive hub of Islamic resources. Participation from Islamic countries is fundamental in the success of the International Islamic Digital Library. It is with utmost pleasure that we invite OIC member countries to participate in this ambitious and mutually benefiting undertaking.
Keywords: Islam -- Computer network resources; Islam -- Collected works